2003
DOI: 10.1103/physreva.67.043805
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear magneto-optical rotation of elliptically polarized light

Abstract: We predict theoretically and demonstrate experimentally an ellipticity-dependent nonlinear magneto-optic rotation of elliptically-polarized light propagating in a medium with atomic coherence. We show that this effect results from hexadecapole and higher order moments of the atomic coherence, and is associated with an enhancement of Kerr and higher orders nonlinearities accompanied by suppression of the other linear and nonlinear susceptibility terms of the medium. These nonlinearities might be useful for quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…This means that we have to "disturb" the exact EIT resonance conditions, by taking slightly different detunings. This is a general conclusion, valid for any atomic level scheme resembling multiple ⌳ systems [26][27][28][29]. If the double EIT-resonance condition is disturbed by a small amount, one remains within the common transparency window and the absorption is still negligible.…”
Section: Fig 2 Probe Absorption and Dispersion ͑␦mentioning
confidence: 74%
See 1 more Smart Citation
“…This means that we have to "disturb" the exact EIT resonance conditions, by taking slightly different detunings. This is a general conclusion, valid for any atomic level scheme resembling multiple ⌳ systems [26][27][28][29]. If the double EIT-resonance condition is disturbed by a small amount, one remains within the common transparency window and the absorption is still negligible.…”
Section: Fig 2 Probe Absorption and Dispersion ͑␦mentioning
confidence: 74%
“…This can be achieved by slightly mismatching the probe and coupling field frequencies yet remaining within the EIT transparency window making the dispersion of the probe field not exactly zero. In this case enhanced Kerr nonlinearities have been observed in the ⌳ configuration [23,24] and predicted in the so-called chain-⌳ configurations [25][26][27][28][29]. By using this second approach Ottaviani et al [29] have shown that large cross-phasemodulations that occur in an "M" configuration may lead to an all-optical two-qubit quantum phase gate (QPG) [1,30], where one qubit gets a phase shift dependent on the state of the other qubit.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental techniques involving NMOR [23] are applied to diverse problems in magnetometry [13,24], quantum and nonlinear optics [23,[25][26][27][28][29], and precision measurements [16,[30][31][32]. Our experiment takes advantage of narrow NMOR resonances related to long-lived, groundstate atomic spin polarization moments [33][34][35][36] which generically appear in atomic systems with slow relax- * Electronic address: derek.jacksonkimball@csueastbay.edu ation of Zeeman coherences (long T 2 ) -precisely those systems most significantly affected by vector light shifts.…”
mentioning
confidence: 99%
“…A possible solution is the enhancement of photon-photon interaction either in cavity QED configurations [2] or in dense atomic media exhibiting electromagnetically induced transparency (EIT) [3]. In this latter case, optical nonlinearities can be produced when EIT is disturbed, either by introducing additional energy level(s) [4,5], or by mismatching the probe and control field frequencies [6,7].…”
mentioning
confidence: 99%
“…A possible solution is the enhancement of photon-photon interaction either in cavity QED configurations [2] or in dense atomic media exhibiting electromagnetically induced transparency (EIT) [3]. In this latter case, optical nonlinearities can be produced when EIT is disturbed, either by introducing additional energy level(s) [4,5], or by mismatching the probe and control field frequencies [6,7].In this letter, we address the feasibility of EIT-based systems for the implementation of a two-qubit quantum phase gate (QPG) for travelling single photons [8,9,10], by means of a full quantum treatment of the system dynamics. In a QPG, one qubit gets a phase conditional to the other qubit state according to the transformation [11,12] |i 1 |j 2 → exp {iφ ij } |i 1 |j 2 where {i, j} = 0, 1 denote the logical qubit bases.…”
mentioning
confidence: 99%